Cross-cultural adaptation of the Arabic Positive and Negative Syndrome Scale in schizophrenia: Qualitative analysis of a focus group. (October 2019) - Amro, Iman; Ghuloum, Suhaila; Mahfoud, Ziyad; Opler, Mark; Khan, Anzalee; Hammoudeh, Samer; Hani, Yahya; Yehya, Arij; Al-Amin, Hassen
As part of a project to translate and validate scales used in the diagnosis and treatment of Arab patients with schizophrenia, this study aimed to explore the experience of clinical research coordinators (CRCs) while administering the Arabic version of the Positive and Negative Syndrome Scale (PANSS) on Arab schizophrenia patients. We previously reported that the Arabic version of PANSS is a valid and reliable tool to assess Arab patients with schizophrenia. Five CRCs and the principal investigator attended focus group discussions on cultural issues in administering the PANSS. A thematic analysis approach was utilized for data coding and analysis. The results identified issues related to the translation of the instrument, the structure of the interview, the cultural sensitivity of some questions, and the procedures for rating items of the PANSS. Qualitative analysis also identified four main themes relevant to clinical assessment of patients from Middle Eastern cultures: religion, beliefs and values, gender, and semantic expressions. In conclusion, researchers or clinicians administering the PANSS scale interview in Arabic should be trained to consider the roles of local dialects, familiarity with abstract thinking, religion, and social constructs when assessing psychosis.